Nitrate reduction by salivary bacteria, glucose metabolism, and lifestyle - Evangelia Morou-Bermúdez; Kai Guo; Jairelisse Morales Morales; Karina Ricart; Rakesh P. Patel; José C. Clemente; Kaumudi Joshipura (Journal of Oral Microbiology)
Background Nitrate reductases (NR) expressed in oral bacteria reduce nitrate to nitrite. Depending on the environmental conditions and types of bacteria present nitrite can be further reduced to ammonium via Dissimilatory Nitrate Reduction to Ammonium (DNRA), or alternatively to nitric oxide (NO), which impacts cardiometabolic health.Objective To evaluate the associations between nitrate reduction by salivary bacteria, clinical markers of glucose metabolism, and lifestyle factors that can modulate the oral environment, potentially impacting DNRA and NR expression.Methods A cross-sectional study was conducted using a convenience sample of 144 participants from the San Juan Overweight Adult Longitudinal Study (SOALS), which includes data on glucose metabolism and lifestyle. DNRA and NR activities were measured in saliva under aerobic or CO2-enriched conditions.Results DNRA activity was inversely associated with insulin resistance (HOMA-IR) [aerobic3rd vs.1st tertile: β=-0.48 (−0.81, −0.15); CO2-enriched3rd vs.1st tertile β=-0.42 (−0.68, −0.17)], fasting blood glucose [aerobic3rd vs.1st tertile β=-0.144 (−0.268, −0.019); CO2-enriched3rd vs.1st tertile: β=-0.070 (−0.130, −0.011)], and 2-h glucose [CO2-enriched3rd vs.1st tertileβ=-0.21 (−0.37, −0.04)]. Current smokers had lower DNRA activity than non-smokers under aerobic conditions [β=-1.55 (−2.96, −0.14)], but higher under CO2-enriched conditions [β = 0.93 (0.15, 1.71)]. Toothbrushing frequency (twice/day vs. once/day) was positively associated with DNRA activity under CO2-enriched conditions [β = 4.11 (1.90, 6.32)] and with aerobic NR activity [β = 1.20, (0.14, 2.27)]. Physical activity was inversely associated with aerobic NR [β=-0.01, (−0.022, −0.003)]. Under CO2-enriched conditions NR was inversely associated with the BMI (β=-0.11, p = 0.007). Aerobic NR was higher when sucrose was added to the assays (NADP vs. sucrose β=-0.74, p = 0.02) and positively associated with salivary nitrate levels (β = 0.002, p = 0.002).Conclusions Nitrate reduction by salivary bacteria is inversely associated with insulin resistance and can be modulated by lifestyle factors. This knowledge could lead to the development of novel, non-invasive approaches for monitoring and preventing diabetes progression.